Transcriptome profile analysis of Indian mustard (Brassica juncea L.) during seed germination reveals the drought stress-induced genes associated with energy, hormone, and phenylpropanoid pathways - Wei, Jinxing (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.